PROTOTYPE LARANGAN PENGENDARA MELEWATI ZEBRA CROSS DI TRAFFIC LIGHT BERBASIS ESP32 CAM - A Muh Idham; Adi Candra; Andi Nurul Faizah (journal Informatika, Multimedia, dan Informasi, 2023)
This research aims to: 1 ) Designing a prototype prohibiting motorists from a zebra crossing at a traffic light based on esp32 cam. 2) Implemented a prototype prohibiting motorists from crossing a zebra crossing at an esp32 cam based traffic light. This study uses action research methods (action research) with planning steps (plan), action (action), and observation. Data collection is done a way : observation, interview, literature riview, documentation. Based on the results of this study it can be concluded that: 1) The Esp32 Cam-Based Zebra Cross Passing prototype in Traffic Light was designed and built using Esp32 Cam, Loop Detector, Relay, Speaker, Dev mini, Cables Jumper, and Blynk. 2) Implementation of the Zebra Cross Based Esp32 Cam at Traffic Light can work well where if the sensor detects a vehicle, the speaker will sound and we can see or monitor it through the Blynk.